Parental Acculturative Stressors and Adolescent Adjustment Through Interparental and Parent-Child Relationships in Chinese American Families. - Hou, Yang; Kim, Su; Wang, Yijie (Journal of Youth & Adolescence, 2016)
Perpetual foreigner stereotype and bicultural management difficulty are two understudied acculturative stressors frequently experienced by Asian Americans. This study expanded the family stress model to examine how parental experiences of these two acculturative stressors relate to measures of adolescent adjustment (depressive symptoms, delinquent behaviors, and academic performance) during high school and emerging adulthood through interparental and parent-child relationship processes. Participants were 350 Chinese American adolescents ( M = 17.04, 58 % female) and their parents in Northern California. Path models showed that parental acculturative stressors positively related to parent-child conflict, either directly (for both mother-adolescent and father-adolescent dyads) or indirectly through interparental conflict (for mother-adolescent dyads only). Subsequently, both interparental and parent-child conflict positively related to a sense of alienation between parents and adolescents, which then related to more depressive symptoms, more delinquent behaviors, and lower academic performance in adolescents, for mother-adolescent and father-adolescent dyads. These effects persisted from high school to emerging adulthood. The results highlight the indirect effects of maternal and paternal acculturative stressors on adolescent adjustment through family processes involving interparental and parent-child relationships.